Local challenges for IWRM in Afghanistan - Thomas, V.; Osmani, A.; Wegerich, Kai (Informa UK Limited, 2011)
Over the past 25 years, there has been a sharp increase in the number and the intensity of use of mills and micro-hydropower units within canal systems in Afghanistan. Before the Soviet occupation, the construction of non-consumptive structures was regulated. Through a case study in one canal along the Taloqan river, the paper shows that an increasing number of poorly designed and badly located structures (including micro-hydropower units) are currently threatening irrigation water availability for downstream areas, as either their unauthorised construction reduce the conveyance capacity of the main canal or their abusive use drains water from the main canal out of the system in its upstream reaches. The article also shows that while relevant initiatives are taken at local and policy level to address the problem, tangible results remain limited owing mainly to limited enforcement capacity.